2019
DOI: 10.1111/epi.16273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of multigene panel testing in adults with epilepsy and intellectual disability

Abstract: Objective To determine the diagnostic yield of a commercial epilepsy gene panel in adults with chronic epilepsy and accompanying intellectual disability, given that genetic evaluation is often overlooked in this group of patients. Methods This is a cross‐sectional study analyzing the results of epilepsy gene panels including up to 185 genes in adult epilepsy patients with intellectual disability, according to Diagnostic and Statistical Manual of Mental Disorders, fifth edition. Patients with acquired structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 34 publications
8
55
1
Order By: Relevance
“…In our study, a genetic diagnosis was made in 13 (11%) of 118 adults, which was similar to the diagnostic yield found in pediatric epilepsy (p = 0.145). However, our yield was slightly lower than that obtained in previous studies in adults, in which a genetic cause was identified in 22 or 23% of cases, respectively (Borlot et al, 2019;Johannesen et al, 2020). The higher yield in the other studies may have been due to most patients also presenting with ID and/or developmental delay.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In our study, a genetic diagnosis was made in 13 (11%) of 118 adults, which was similar to the diagnostic yield found in pediatric epilepsy (p = 0.145). However, our yield was slightly lower than that obtained in previous studies in adults, in which a genetic cause was identified in 22 or 23% of cases, respectively (Borlot et al, 2019;Johannesen et al, 2020). The higher yield in the other studies may have been due to most patients also presenting with ID and/or developmental delay.…”
Section: Discussioncontrasting
confidence: 90%
“…This may be the reason why patients with focal epilepsy were more likely to accompany with ID than patients with generalized epilepsy in our study (9/49, 18.5% vs. 11/101, 10.9%). Evidence from our study and the studies of some others suggested that epilepsy patients with ID were significantly more likely to have a positive result (Borlot et al, 2019;Johannesen et al, 2020). Thus, at least in part, explain that the diagnostic rate is higher in focal vs. generalized epilepsy in our study.…”
Section: Discussionsupporting
confidence: 65%
“…For other EOEEs, gene panels or whole exome/genome sequencing (WES/WGS) analyses can lead to a diagnostic yield varying between 30% and 70% 70 . A recent study in adults with treatment-resistant epilepsy and intellectual disability using the same wide sequencing approach had a similar diagnostic rate, highlighting a significant unmet clinical need in older patients 71 .…”
Section: Assessment and Diagnosismentioning
confidence: 94%
“…We read with great interest the article entitled “Utility of Genetic Testing for Therapeutic Decision‐Making in Adults With Epilepsy” by Johannesen and colleagues, investigating 200 patients with gene panels over 6 years 1 . Their work achieved the same diagnostic yield as a smaller cohort published by us last year 2 . Both studies had similar study populations, consisting of adults with epilepsy, mostly accompanied by intellectual disability and medically refractory seizures.…”
mentioning
confidence: 99%
“…Given that the genetic basis for many adults with unexplained seizures is still unsolved, it would be interesting to learn whether these patients could benefit more from distinct diagnostic approaches. Copy number variants and coding exon analysis are not enough to narrow the current diagnostic gap 1,2,6 . Whole‐genome sequencing is one strategy, despite the variant‐interpretation challenges.…”
mentioning
confidence: 99%